Description of Acaralox latifolia n. sp. (Acari: Trombidiformes: Eriophyoidea) on water bamboo from Taiwan - Huang, Kun-Wei; Chang, Shu-Chen; Hsieh, Tzay-Tien; Shentu, Hsuan (Zootaxa, 2022)
Water bamboo, Zizania latifolia (Griseb.), Poaceae, is the major crop in Puli Township, Taiwan. Following some unknown mite infestations causing leaf curling symptoms first observed in 2018, water bamboos experienced a dramatic crop yield. Our morphological evaluation revealed their infestation with a new species of eriophyoid mite, Acaralox latifolia n. sp. (Acari: Trombidiformes: Eriophyoidea). Here, we described and illustrated this new species and provided its scanning electronic micrographs and DNA sequences of COI and ITS regions. This is the first record of the genus Acaralox from Taiwan.